GELIAT SYIAH, PERUBAHAN PAHAM DAN PERILAKU KEAGAMAAN MAHASISWA MUSLIM DI KOTA MAKASSAR - Sabara Sabara (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
During the last two decades, there has been a phenomena of Syiah massive development in Makassar. The main actors of the movements are moslem students. This research’s objectives are to describe its development, cadering process, change of undertanding and behavior on religious life of moslem students in that town. This research was done qualitatively and descriptive type of analysis for getting various data/information from students. This study finds that Syiah is populer among students but they look it from different perspectives in judgment and behaving. The spread of Syiah in this town supported by IJABI as a mass organisation that has nine Syiah foundations and some study groups in Campus. Syiah penetration was done by intellectual approaches and transformation of Iran Revolution make arose of students` interest, especially activists. Development of Syiah among students makes changes on behavior, religious behaviors which in line with Syiah dogma.